Can melanoma therapy change attitudes toward prevention and tanning?. Issue 3 (23rd October 2013) - Konkolova, Radmila; Provaznikova, Doc Hana; Jirakova, Anna; Hercogova, Jana
Abstract Malignant melanoma is the most lethal skin cancer whose incidence is increasing worldwide. Important is knowledge of risk factors, early diagnosis, long‐term follow‐up on confirmed melanoma cases and prevention. In this study, we tested melanoma patients' attitudes toward solar radiation and perception of the value of follow‐up. The present cross‐sectional epidemiological study was carried out in a group of patients diagnosed with stage I and II of malignant melanoma (n = 124). They were monitored for at least 1 year. The research was carried out by anonymous questionnaire. The results revealed that the respondents welcomed the opportunity of follow‐up care. Its benefits were said to outweigh the inconvenience of repeated checkups. However, the esthetic importance of a suntan was still considered quite high. Substantial reserve was found in the use of sunscreen. The need for wide public education and the protection against excessive contact with solar radiation is evident. Regular monitoring seems to be just as important.